Prinsip Moderasi Beragama dalam Kehidupan Bermasyarakat di Desa Sungai Batang - Ulfa, Nikmatul; Sari, Nur Lailan (JURNAL PAI: Jurnal Kajian Pendidikan Agama Islam, 2024)
Ethnic and cultural diversity is a characteristic of Indonesia. Indonesia has various religions with Islam being the majority. In religion, there is a need for balance to create justice, as is done by the Sungai Batang Village Community. Sungai Batang Village is a division of Ketemputih Village. The area of Sungai Batang Village is around 37 km with a population density of 1,665 people and Islam is the majority religion. The moderation carried out by the people of Sungai Batang Village is a form of tolerance by not distinguishing between views on ethnicity and religion. The research aims to analyze the concept of religious moderation which is carried out to obtain the principles applied to religious moderation in the lives of the people of Sungai Batang Village. The method used in the research uses qualitative methods using primary and secondary data samples. After analyzing, the results are obtained in the form of principles that are applied in life in the form of balance (tawazun), justice (i’tidal), tolerance (tasamuh), middle way (tawassuth), deliberation (syura), reform (ishlah), adab. (tahadhdhur), equality (musawah), priority (aulawiyah), dynamic and innovative (tathawwur wa ibtikar).